2021
DOI: 10.1186/s12905-021-01211-w
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities associated with cervical cancer screening programs in a low income, high HIV prevalence context

Abstract: Background Cervical cancer is a leading cause of death among Cameroon women. The burden of cervical cancer is in part traceable to the inadequate understanding of socio-contextual determinants of access to screening and prevention opportunities. We explored multilevel individual, community and structural factors that facilitate or inhibit cervical cancer prevention in women at risk in a low-income, high HIV prevalence context. Methods We utilized a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 26 publications
5
41
0
Order By: Relevance
“…HICs have been able to reduce cervical cancer incidence and mortality; however, LMICs continue to bear the burden of the disease [16]. Furthermore, in HICs, HPV as the primary test for cervical cancer screening has gradually been introduced [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HICs have been able to reduce cervical cancer incidence and mortality; however, LMICs continue to bear the burden of the disease [16]. Furthermore, in HICs, HPV as the primary test for cervical cancer screening has gradually been introduced [17].…”
Section: Discussionmentioning
confidence: 99%
“…The Abbott RealTime High-Risk HPV assay (Abbott Molecular GmbH & Co. KG, Wiesbaden, Germany) is a real-time PCR assay that detects 14 hrHPV DNA (16,18,31,33,35,39,45,51,52,56,58,59, 66 and 68) and genotypes only HPV types 16 and 18 from the other 12 hrHPV (non-HPV 16/18) types. A volume of 800 µL of healthcare worker and self-collected samples was transferred into Abbott m2000 Master-Mix tubes, respectively, and loaded into the Abbott m2000sp (Sample Preparation) system for extraction using the mSample Preparation System DNA kit.…”
Section: Abbott Realtime High-risk Hpv Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…A body of literature supported the fear of discrimination as an important barrier for health-seeking behaviour among the HIV-positive population (Ongtengco et al, 2020). Women living with HIV refuse to participate in community or workplace-organised health-examination programmes because of fear of moral judgement (Adedimeji et al, 2021). This observation was consistent with the finding in the current study that reasons reported by non-screened women for not being screened included 'medical discrimination' and 'being worried T A B L E 7 Logistic-regression analysis for previous uptake of cervical cancer screening (n = 213) about AIDS disclosure'.…”
Section: Discussionmentioning
confidence: 99%
“…Effective screening efforts are associated with earlier stages at diagnosis, and detection of cancers that are more amenable to curative treatment, leading to better outcomes (67). There are several barriers to the secondary prevention of cancer in LMICs including limited infrastructure, few trained personnel, high cost of equipment purchase and maintenance, and inadequate training of healthcare providers (68,69). In areas where screening programs exist, some LMICs experience a simultaneous over-and under-utilization of these services; screening resources and personnel are often clustered in urban settings, where there is a large population base and high demand, limiting opportunities for screening in rural settings.…”
Section: Secondary Prevention Of Cancer In Lmicsmentioning
confidence: 99%